A method of producing biodiesel using oil containing high content of free fatty acids - Yap, Taufiq Yun Hin; Bahari, Aqilah Noor; Basri, Mahiran (2011)
A method of producing biodiesel comprises the steps of reacting an oil with an alcohol under heating in the presence of solid catalysts; wherein the oil has free fatty acid content not less than 3% by weight percentage and the solid catalysts are calcined bismuth vanadyl phosphates.